2017
DOI: 10.1371/journal.pone.0179036
|View full text |Cite
|
Sign up to set email alerts
|

Effects of salinity on gonadal development, osmoregulation and metabolism of adult male Chinese mitten crab, Eriocheir sinensis

Abstract: As a catadromous species, salinity is a key parameter that affects gonadal development of Chinese mitten crab Eriocheir sinensis during reproductive migration. It is however unclear the effects of salinity on the gonadal development of male E. sinensis as well as their physiological responses to salinity during reproductive migration. This study investigated the effects of four salinities (0 ‰, 6 ‰, 12 ‰ and 18 ‰) on gonadal development, osmoregulation and metabolism of adult male E. sinensis over a 40-day per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
56
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(60 citation statements)
references
References 50 publications
4
56
0
Order By: Relevance
“…All crabs were treated with cold shock method to minimize suffering, then around 2 mL hemolymph was withdrawn from each crab sample by inserting a 1.0 mL syringe at the base of the third walking leg and all hemolymph samples were stored at −40°C for later analysis. It is known that E. sinensis has six pairs of gills, previous studies have shown that the first 3 pairs of the gills (pairs 1–3, also known as anterior gills) are responsible for respiration while pairs 4–6 of gills (posterior gills) are specified for osmoregulation (Long et al, 2017b ). Therefore, in this study, the pairs 5 posterior gills were sampled and snap frozen in liquid nitrogen and stored at −80°C for the Na + /K + -ATPase activity and its mRNA expression analysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All crabs were treated with cold shock method to minimize suffering, then around 2 mL hemolymph was withdrawn from each crab sample by inserting a 1.0 mL syringe at the base of the third walking leg and all hemolymph samples were stored at −40°C for later analysis. It is known that E. sinensis has six pairs of gills, previous studies have shown that the first 3 pairs of the gills (pairs 1–3, also known as anterior gills) are responsible for respiration while pairs 4–6 of gills (posterior gills) are specified for osmoregulation (Long et al, 2017b ). Therefore, in this study, the pairs 5 posterior gills were sampled and snap frozen in liquid nitrogen and stored at −80°C for the Na + /K + -ATPase activity and its mRNA expression analysis.…”
Section: Methodsmentioning
confidence: 99%
“…As such, there are likely gender differences in physiological responses to salinity changes during reproductive migration and gonadal development, which necessitates studies on salinity effects on gonadal development of E. sinensis being carried out separately for males and females. Our recent studies have reported the effects of long-term salinity adaptation on gonadal development, osmoregulation and metabolism of adult male E. sinensis (Long et al, 2017b ), however it remains unknown the physiological responses and ovarian development of female E. sinensis subjected to different salinity conditions. Therefore, the present study comprehensively investigated the effects of long-term exposure to different salinities on ovarian development, hemolymph osmolality and major ion as well as free amino acid concentrations, gill Na + /K + -ATPase activity and fatty acids profile, as well as a range of metabolic and antioxidant indices in hemolymph and hepatopancreas of the female E. sinensis following puberty molt.…”
Section: Introductionmentioning
confidence: 99%
“…A total of eight crabs were randomly sampled from each treatment and weighted using a digital balance (precision = 0.01 g). According to the method of Long, Wu, Zhao, Ye, et al (), all crabs were treated with cold shock method to minimize suffering, and then around 3 ml haemolymph was withdrawn by inserting a syringe at the base of the fourth walking limb of each crab and stored in two 2‐mL tubes at −80℃ for later analysis of antioxidant and immune indices. The hepatopancreas and muscle from each crab were carefully dissected out and weighted separately before stored at −40℃ for later biochemical analysis.…”
Section: Methodsmentioning
confidence: 99%
“…However, studies of isosmotic media in other invertebrates have been conducted as the results of Anggoro and Muryati (2007) showed that salinity of the osmotic medium significantly affected Ca-chorionase enzyme activity, energy efficiency and efficiency of egg hatching Metapenaus elegans. Another research showed that salinity fluctuation greatly affected the development of male gonads crab Eriocheir sinensis, increasing osmolarity and ionic concentration in hemolymph (Long et al, 2017). …”
Section: Relationship Between Gonad Maturity Stage and Level Of Osmotmentioning
confidence: 99%